Change in Children’s Physical Activity: Predictors in the Transition From Elementary to Middle School - Pate, Russell R. (Am J Prev Med, 2019)
INTRODUCTION: Interventions to promote physical activity in children should be informed by knowledge of the factors that influence physical activity behavior during critical developmental transitions. The purpose of this study is to identify, from a comprehensive, multidomain set of factors, those that are associated with change in objectively measured physical activity in children as they transition from elementary to middle school. METHODS: The study used a prospective cohort design, with children observed in fifth, sixth, and seventh grades. Growth curve analyses were used to examine associations between exposure variables measured at baseline and children’s physical activity across three observations. A total of 828 children, aged 10.6 (SD=0.5) years at baseline provided physical activity data in fifth grade and at one or both follow-ups. Exposure variables assessed child characteristics, parent characteristics, home characteristics, social factors, school environment, and community characteristics. Physical activity was measured via accelerometry. Data were collected in two school districts in South Carolina in 2010–2013 and analyzed in 2017. RESULTS: Variables measured within the child, parent/home, and community domains were positively associated with children’s physical activity as they transitioned from fifth to seventh grade. These included parent encouragement of physical activity, parental support for physical activity, child sports participation, parent’s report of the child’s physical activity level, the child’s time spent outdoors, social spaces for physical activity in the community, and the number of physical activity facilities that were proximal to the child’s home. CONCLUSIONS: Interventions designed to increase children’s physical activity should include strategies that target multiple domains of influence.